Ranking of Innovation Related Factors Influencing Artificial Intelligence Performance - Mohammed Sharif Ismail, Jalal Ismail; Nazrin Muhammad, Mohd; Abo Mosali, Najmaddin (International Journal of Sustainable Construction Engineering and Technology, 2022)
This paper presents a study on ranking of 27 identified innovation related factors which influencing Artificial Intelligence (AI) performance in UAE. These factors were clustered into four groups namely process innovation; management capabilities; personal expertise and organization structure. A questionnaire was designed based on these factors where respondents were required to gauge the influence of these factors using Likert scale. Respondents were from three UAE organisations which are Dubai Police, Dubai Electricity & Water Authority Dewa, and Emirates Integrated Telecommunications Company. A total of 384 valid responses from the questionnaire survey were analysed for its reliability using Cronbach alpha criterion. Then the data was analysed for its mean score and standard deviation values for each of the factors to determine the rank of each factor and also its influence on the organisation performance. The study found that the mean scores for the factors are in the range from 2.90 to 3.56 while for the average mean score for the groups are from 3.15 to 3.44. the study also found that two factors which are management capabilities and artificial intelligence are highly influencing the organisational performance while the other three factors which process innovation, personal expertise and organisational structure are moderately influencing the UAE organisational performance. The findings of this study will ably provide a better understanding of innovation related factors and how it affects overall performance.